PENGEMBANGAN BUDIDAYA IKAN LELE DAN NILA MELALUI PENERAPAN TEKNOLOGI MODIFIKASI PAKAN DENGAN EKSTRAK DAUN KATUK, PEMIJAHAN BUATAN, DAN SEXREVERSAL DI KELURAHAN KARANG HARAPAN KOTA TARAKAN KALIMANTAN UTARA - Diana Maulianawati; Awaludin Awaludin; Meylin Rachmawati (Indonesian Collaboration Journal of Community Services, 2021)
Catfish and tilapia are freshwater fish whose production continues to be increased every year due to high market demand. High market demand encourages cultivators to continue to innovate in accelerating production. Technology must be applied to increase production. Tarakan City produces freshwater fish such as catfish and tilapia. The fish cultivator group (POKDAKAN) "Raja Catfish Karang Harapan" is one of the conventional freshwater aquaculture groups in Tarakan. To overcome the continuous availability of seeds for catfish, it is necessary to improve the quality of the broodstock. Improvement of seed quality can be approached by increasing broodstock performance through good feeding, for example by adding katuk extract which has high fatty acids and steroids to help accelerate gonadal maturation and injection of ovaprim hormone to assist artificial spawning. In tilapia to produce fast growth, monosex cultivation must be carried out. To produce monosex culture, it can be done by adding the hormone 17?-methyltestosterone (17?-mt) and using celery extract because it contains steroids that can make fish male. As a result of this activity, partners were able to make feed with the addition of katuk extract and injection of ovaprim hormone for catfish brooders as well as monosex cultivation using celery extract and the hormone 17?-methyltestosterone (17?-mt). It is hoped that the training that will be carried out with the group (POKDAKAN) "Raja Lele Karang Harapan" will be the first step to increase catfish seed production and tilapia cultivation in the city of Tarakan throughout the year